1999
DOI: 10.1021/la990024n
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of Metal Oxide Surfaces. 1. Surface Characterization and Cell Response

Abstract: Silicon and titanium oxide surfaces (SiO2/Si and TiO2/Ti) were covalently modified with bioactive molecules (e.g., peptides) in a simple three-step procedure. Bioactive surfaces were synthesized by first immobilizing N-(2-aminoethyl)-3-aminopropyl-trimethoxysilane (EDS) to either polished quartz disks, polished silicon wafers, or sputter-deposited titanium films. Subsequently, a maleimide-activated surface amenable to tethering molecules with a free thiol (e.g., cysteine) was created by coupling sulfosuccinimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 69 publications
7
139
0
3
Order By: Relevance
“…23 Furthermore, these data agree with the reported threshold (0.01 < G attach/spread ¼ 0.62 pmol/cm 2 ) required for maximal osteoblast attachment and spreading on amino-functionalized SiO 2 /Si surfaces modified with the bsp-RGD(15) peptide. 24 Although the threshold for maximal alkaline phosphatase activity was the same as for attachment and proliferation, normalization of the activity to cell number suggests that this is not causative, but coincidental. Although no difference was found in ultimate activity between the 0.1 and 10 pmol/cm 2 bsp-RGD(15) modified surfaces, the time to reach that maximum shifted (14 vs. 21 days).…”
Section: Discussionmentioning
confidence: 98%
“…23 Furthermore, these data agree with the reported threshold (0.01 < G attach/spread ¼ 0.62 pmol/cm 2 ) required for maximal osteoblast attachment and spreading on amino-functionalized SiO 2 /Si surfaces modified with the bsp-RGD(15) peptide. 24 Although the threshold for maximal alkaline phosphatase activity was the same as for attachment and proliferation, normalization of the activity to cell number suggests that this is not causative, but coincidental. Although no difference was found in ultimate activity between the 0.1 and 10 pmol/cm 2 bsp-RGD(15) modified surfaces, the time to reach that maximum shifted (14 vs. 21 days).…”
Section: Discussionmentioning
confidence: 98%
“…The most common ones use silane coupling agents that react with the oxide layer formed on metal surfaces. [21][22][23][24][25][26][27] In most cases, the silane coupling agent consists of a trimethoxy or triethoxy silane where the fourth bond of the silane molecule is an organo-functional group that can be further reacted to attach a variety of organic compounds or polymers. The methoxy or ethoxy groups hydrolyze, leaving the silanol to react with the metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…These and other adhesive proteins contain short peptide sequences such as RGD, REDV, YIGSR, PHSRN, KNEED, and PRRARV, [37][38][39][40][41][42][43][44][45][46][47][48][49] which are bound by the integrins to promote cell adhesion, spreading, and proliferation. Although significant work has been done to attach proteins and peptides to metal oxide particles 21 and silicon oxide on Si wafers, 26 relatively little research has been reported on attachment of polypeptides to macroscopic metallic surfaces. 23,24,26,27,50 -53 With respect to short peptides, Xiao et al 27 attached an RGDcontaining peptide to titanium using aminopropyl silane and maleimide chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maleimide heterobifunctional crosslinker that allows for a selective conjugation with -NH 2 and -SH groups of peptides [8,9] was applied to 3-aminopropyltriethoxysilane (APTES) SAMs. A large, residual non-specific interaction was identified on these maleimide-functional substrates that could be minimized by a simple modification of the attachment chemistry.…”
Section: Introductionmentioning
confidence: 99%